An examination of Andre Jolivet’s Concertino for trumpet, Oskar Bömhe’s Concerto for trumpet in F minor, Tomoso Albinoni’s Sonata á 6 con tromba, and Manuel de Falla’s Suite of old Spanish dances - Klinefelter, Katherine Lee (Kansas State University, 2011)
This Master’s report focuses on analyzing the four works performed on the author’s Master’s recital on April 10, 2011, from a biographical, historical, theoretical, and technical standpoint. These works include André Jolivet’s Concertino for Trumpet, Oskar Böhme’s Concerto for Trumpet in F Minor, op. 18, Tomaso Albinoni’s Sonata á 6 con Tromba, and Manuel de Falla’s Suite of Old Spanish Dances.
Keywords: Bömhe; Jolivet; Albinoni; Falla; Trumpet; Music (0413); Musical Performances (0943); Music Education (0522)